Inhibition of (Pro)renin Receptor-Mediated Oxidative Stress Alleviates Doxorubicin-Induced Heart Failure - Du, Xiao-yi; Xiang, Dao-chun; Gao, Ping; Peng, Hua; Liu, Ya-li (Frontiers in Oncology, 2022)
Aim Clinical utility of doxorubicin (DOX) is limited by its cardiotoxic side effect, and the underlying mechanism still needs to be fully elucidated. This research aimed to examine the role of (pro)renin receptor (PRR) in DOX-induced heart failure (HF) and its underlying mechanism. Main Methods Sprague Dawley (SD) rats were injected with an accumulative dosage of DOX (15 mg/kg) to induce HF. Cardiac functions were detected by transthoracic echocardiography examination. The levels of lactate dehydrogenase (LDH) and creatine kinase (CK) in serum were detected, and oxidative stress related injuries were evaluated. Furthermore, the mRNA expression of PRR gene and its related genes were detected by real-time PCR (RT-PCR), and protein levels of PRR, RAC1, NOX4 and NOX2 were determined by Western blot. Reactive oxygen species (ROS) were determined in DOX-treated rats or cells. Additionally, PRR and RAC1 were silenced with their respective siRNAs to validate the in vitro impacts of PRR/RAC1 on DOX-induced cardiotoxicity. Moreover, inhibitors of PRR and RAC1 were used to validate their effects in vivo. Key Findings PRR and RAC1 expressions increased in DOX-induced HF. The levels of CK and LDH as well as oxidative stress indicators increased significantly after DOX treatment. Oxidative injury and apoptosis of cardiomyocytes were attenuated both in vivo and in vitro upon suppression of PRR or RAC1. Furthermore, the inhibition of PRR could significantly down-regulate the expressions of RAC1 and NOX4 but not that of NOX2, while the inhibition of RAC1 did not affect PRR. Significance Our findings showed that PRR inhibition could weaken RAC1-NOX4 pathway and alleviate DOX-induced HF via decreasing ROS production, thereby suggesting a promising target for the treatment of DOX-induced HF.